Development of Flipbook Learning Media for Prayer Guidance as a Tool for Behavior Management in Children with ASD - Laili, Lina Nur; Gultom, Cindy Aulia; Puspita , Endang (GRAB KIDS: Journal of Special Education Need, 2026)
Children with autism are children who experience developmental disorders of brain function characterized by impairments in communication, social interaction, and behavior. The various impairments experienced by students with autism affect their understanding of the lessons taught. Therefore, media designed in an attractive manner is needed to make it easier for children with autism to understand lessons in accordance with their characteristics. The purpose of this study was to develop a flipbook learning medium for prayer guidance to manage the behavior of autistic children. The method used in this study was Research and Development using the ADDIE model. The product developed has been reviewed by subject matter experts and media experts, who have determined that the developed media is suitable for use by autistic children